Prevalence of Irritable Bowel Syndrome Symptoms Among Medical Students at University of Benghazi - Ferjani , Safaa Farag; Ferjani , Marwa Farag (Scientific Journal of University of Benghazi, 2023)
Aim: To determine the prevalence of irritable bowel syndrome among medical students at the University of Benghazi using Rome IV criteria, and to compare the results between students based on their gender and academic year, whether basic (from the first to the third year) or clinical (fourth and fifth years). Material and Methods: A cross-sectional observational study was carried out among medical students at the University of Benghazi using Rome IV criteria. Data was collected from June 10th, 2022, to August 31st, 2022, and a semi-structured questionnaire was used. The sample included students from the first year to the fifth year of medicine. Results: This study included data from 381 medical students, whose ages ranged from 19 to 39. The prevalence of irritable bowel syndrome was found to be 16.01%. Our study found no association between IBS symptoms and gender (p = 0.79). Additionally, no association was observed between IBS symptoms and academic year (p = 0.076), coffee consumption (p = 0.4), as well as smoking (p = 0.9). Conclusion: The prevalence of irritable bowel syndrome was more observed in females in this study; however, we did not find a significant statistical difference between males and females in the prevalence of IBS. Additionally, there was no significant statistical difference in the prevalence of IBS among medical students whether they were in their basic years or clinical years. Furthermore, in our study, IBS was related neither to coffee nor to cigarette smoking.